Enforcement of regulation, informal labor and firm performance - Rita Almeida; Pedro Carneiro (Centre for Microdata Methods and Practice (cemmap), 2006)
This paper investigates how enforcement of labor regulation affects the firm's use of informal labor and firm performance. Using firm level data on informal employment and firm performance, and administrative data on enforcement of regulation at the city level, we show that in areas where law enforcement is stricter firms employ a smaller amount of informal employment. Furthermore, by reducing the firm's access to unregulated labor, stricter enforcement is also associated with lower labor productivity. We control for different regional and firm characteristics, and we instrument enforcement with a measure of the access of labor inspectors to firms. Taken together, our findings suggest that increased access to labor flexibility significantly improves firm performance.
Keywords: J3; J6; O17; 330; Informal Sector; Labor Markets; Regulation; Productivity; Informeller Sektor; Arbeitsnachfrage; Arbeitsmarktpolitik; Personalbeschaffung; Brasilien